1991
DOI: 10.1007/bf00327275
|View full text |Cite
|
Sign up to set email alerts
|

Localization of hydroxyindole O-methyltransferase-synthesizing cells in bovine epithalamus: immunocytochemistry and in-situ hybridization

Abstract: Hydroxyindole O-methyltransferase (HIOMT)-immunoreactive cells and melatonin synthesis were demonstrated in bovine epithalamus (including the pineal gland) with monoclonal antibodies and cRNA probes to HIOMT. The HIOMT-immunoreactive product was present in the cytoplasm of pinealocytes. All identifiable pinealocytes were clearly labeled in the pineal gland. The expression of the HIOMT gene was first identified in pinealocyte cytoplasm by in-situ hybridization (ISH). The distribution of the hybridization-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…The expression of HIOMT in the cells of the stalk and deep pineal demonstrates that they are able to synthesise MEL. S-antigen -immunoreactivity has indicated that pineal cells of the deep pineal project to adjacent central areas of the brain in some species, such as the Djungarian hamster (Korf et al 1986), the mouse (Korf et al 1990) and cattle (Sato et al 1991), but not in the hedgehog, Mongolian gerbil, cat or rat (Korf et al 1985). In the present study, we have not observed extra-pineal labelling resulting from axon-like projections of pinealocytes, thus confirming the findings in the rat as reported by Korf et al (1985).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of HIOMT in the cells of the stalk and deep pineal demonstrates that they are able to synthesise MEL. S-antigen -immunoreactivity has indicated that pineal cells of the deep pineal project to adjacent central areas of the brain in some species, such as the Djungarian hamster (Korf et al 1986), the mouse (Korf et al 1990) and cattle (Sato et al 1991), but not in the hedgehog, Mongolian gerbil, cat or rat (Korf et al 1985). In the present study, we have not observed extra-pineal labelling resulting from axon-like projections of pinealocytes, thus confirming the findings in the rat as reported by Korf et al (1985).…”
Section: Discussionmentioning
confidence: 99%
“…The animal with the largest live weight and metabolic weight (number 10) possessed a pineal gland of weight (265mg) close to that of the mean value (251.4 ± 83.1mg) presented in this study, confirming the study of Volrath (1979) where the metabolic weight has no influence on the pineal weight. Sato et al (1991) further states that the cells present in the habenular commissura possess secretory activity and that the pineal gland of the bovine communicates with the third ventricle. In a similar manner, in buffalos, the gland communicates with the lumen of the stem and the third ventricle.…”
Section: Anatomy Of the Pineal Glandmentioning
confidence: 99%
“…In some rodent species the sympathetic fibers spread out of the pineal gland toward the habenular nuclei (Korf et al, 1990). In some species, a few pinealocytes of the deep pineal gland project to neighboring central structures (the habenular nucleus, the pretectal areas) where they make synapses (Korf et al, 1986(Korf et al, , 1990Sato et al, 1991). The putative transmitters involved have not been identified, but this observation suggests that the pineal gland could exert its influence by a neuronal pathway in addition to the MEL endocrine pathway.…”
Section: Multiple Regulation Of Pineal Melatonin Synthesis In Mammalsmentioning
confidence: 99%